2015
DOI: 10.4238/2015.august.3.1
|View full text |Cite
|
Sign up to set email alerts
|

Association between the rs4753426 polymorphism in MTNR1B with fasting plasma glucose level and pancreatic β-cell function in gestational diabetes mellitus

Abstract: ABSTRACT. We investigated the association between rs4753426 single nucleotide polymorphisms in the melatonin receptor 1B (MTNR1B) gene and the risk of developing gestational diabetes mellitus (GDM). A total of 516 gravidas (186 with GDM and 330 non-diabetic controls) were enrolled in the study. Genotype and allele frequencies of rs4753426 in the MTNR1B gene were detected by DNA sequencing. Fasting plasma glucose and fasting insulin levels were measured to calculate the homeostasis model assessment for insulin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Previous case-control and meta-analysis studies and GWAS on global ethnically diverse populations have confirmed that the rs10830963 and rs1387153 variants in MTNR1B are positively associated with GDM as major risk factors. 14,15,19,23,25-28,46-51 A recent study confirmed that the G allele of rs10830963 is strongly associated with glycemic traits in GDM. 47 In addition the MTNR1B rs10830963 variant, in interaction with prepregnancy BMI, was reported as a predictive genetic marker for the need of antenatal insulin therapy in GDM.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous case-control and meta-analysis studies and GWAS on global ethnically diverse populations have confirmed that the rs10830963 and rs1387153 variants in MTNR1B are positively associated with GDM as major risk factors. 14,15,19,23,25-28,46-51 A recent study confirmed that the G allele of rs10830963 is strongly associated with glycemic traits in GDM. 47 In addition the MTNR1B rs10830963 variant, in interaction with prepregnancy BMI, was reported as a predictive genetic marker for the need of antenatal insulin therapy in GDM.…”
Section: Discussionmentioning
confidence: 81%
“…The human genome project discovered MTNR1B gene SNPs, including rs1387153 (chr11:92940662) and rs10830963 (chr11:92975544), that were associated with an increased risk of diabetes development. 19 The prevalence of GDM in Saudi women is 18.7%, 20 and the major factors contributing to the risk of GDM in this population are a lack of exercise and poor dietary control; the prevalence of obesity in Saudi Arabia is documented at 68%. 1 According to a recent meta-analysis, 14,15 no studies on the MTNR1B gene have been conducted in Saudi populations, or in other Arab/Middle Eastern populations.…”
Section: Introductionmentioning
confidence: 99%
“…However, these changes worsen insulin resistance in pregnant women with GDM. 27 Any alteration in placental development or function may contribute to insulin resistance; therefore, the placenta is a good model to study changes in metabolic programming in women with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin receptor 1B (MTNR1B) is located on human chromosome 11q14.3 and encodes MT2, one of the 2 high-affinity forms of the melatonin receptor [30,31]. MTNR1B is principally expressed in the retina, brain, and pancreatic cells; and is involved in the regulation of insulin release, circadian rhythms, and blood glucose homeostasis by modifying the melatonin-signaling pathway [32]. A recent meta-analysis that included the MTNR1B rs1387153, rs4753426, and rs10830963 loci in a case-control study with 23 participants of Caucasians origin and individuals in Asia and Mexico, findings indicated that the rs1387153, rs4753426, and rs10830963 polymorphisms were associated with a widely regional susceptibility to GDM [33].…”
Section: Genes Involved In β-Cell Function and Insulin Secretionmentioning
confidence: 99%